American anatomies : theorizing race and gender - Wiegman, Robyn (New Americanists., 1995)
"In this brilliantly combative study, Robyn Wiegman challenges contemporary clichés about race and gender, a formulation that is itself a cliché in need of questioning. As part of what she calls her "feminist disloyalty," she turns a critical, even skeptical, eye on current debates about multiculturalism and "difference" while simultaneously exposing the many ways in which white racial supremacy has been reconfigured since the institutional demise of segregation. Most of all, she examines the hypocrisy and contradictoriness of over a century of narratives that posit Anglo-Americans as heroic agents of racism's decline. Whether assessing Uncle Tom's Cabin, lynching, Leslie Fiedler's racialist mapping of the American novel, the Black Power movement of the 60s, 80s buddy films, or the novels of Richard Wright and Toni Morrison, Wiegman unflinchingly confronts the paradoxes of both racism and antiracist agendas, including those advanced from a feminist perspective